Variation in mycorrhizal specificity in Tiger orchids (Grammatophyllum spp.) - Ahmad Bedawi, Salifah Hasanah (2012)
Grammatophyllum seeds are minute and lack endosperm. As their other orchid’s counterpart, the seeds are dependent on mychorrhizal fungi for seed germination in nature. Their nutrients uptake from substrate was assisted by preferable fungal symbionts. Introducing a compatible mycorrhiza into a site may facilitate the establishment of self sustaining populations. However this can only be performed if the orchid is present at the target localities or only when the seedlings that were cultured symbiotically were reintroduced as they can serve as both plant material and a source of mycorrhiza inoculums. To determine these fungal symbionts, fungal isolation was conducted on three species of host plant namely G. speciosum, G. scriptum and G. stapeliiflorum, all native to Malaysia. A total of 59 isolates of different species of fungus were isolated from the host plants. Molecular identification using ITS1 and ITS4 as the primers was made to these isolates. Results of the identification showed that the roots of mature Grammatophyllum spp. were the habitat of various fungal taxa consisting of both common orchid mycorrhizas and ubiquitous fungal taxa. Diversity index showed that G. speciosum harbored the most fungal taxa compared to G. scriptum and G. stapeliiflorum with value of 3.218 indicating the fungal preferences. Seed of G. speciosum and G. stapeliiflorum were used to determine the specificity of fungus relationship using fungal isolated from roots of G. speciosum, G. stapeliiflorum and G. scriptum. The result obtained from the test demonstrated that seeds of G. speciosum showed the highest volume increment when co-cultured with Aspergillus niger, Paecilomyces lilacinus A. fumigatus, Trichoderma asperellum. and an unidentified fungal endophyte. This result shows that specificity of G. speciosum towards mycorrhizas preferences was quite broad considering not all of these fungi were isolated from G. speciosum roots. An even wider specificity was exhibited by G. stapeliiflorum. Having performed the same germination test as G. speciosum seeds, the seeds of G. stapeliiflorum developed a symbiotic relationship with more numbers of mycorrhizas. The initial development of G. stapeliiflorum seed was assisted by 29 of 59 mycorrhizas isolated from different hosts. Based on germination tests, the P. lilacinus and A. fumigatus, were the most effective orchid mycorrhizas to promote seed germination of tropical orchid, G. speciosum and G. stapeliiflorum. Nevertheless, the difference between volume of symbiotic and asymbiotic (control) seed germination was not high, and the final protocorm development stage was not sufficient enough for propagation and conservation The phylogeny tree showed that all these symbiotic mycorrhizas shared a common class namely Eurotiomycetes, including the unidentified fungi. It can be concluded that Grammatphyllum spp. were specialist toward Class of Eurotiomycetes but are generalist toward the members of the class. The specificity in this broadly associating orchid most likely due to the tendency for Grammatophyllum spp. to be colonized by multiple mycorrhizal fungi.